Upaya Penanggulangan Tindak Pidana Pemalsuan dan Pengedaran Uang Palsu di Kota Kupang : Studi Kasus di Polsek Kelapa Lima - Gideon Tasi; Aksi Sinurat; Karolus Kopong Medan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The need for such a large amount of money causes some people to try to get as much money as possible even using illegal means. Such illegal acts can be crimes against the currency itself, such as counterfeiting money which is included in illegal practices that violate the law. One of the modes used is by buying and selling using counterfeit money. This study is an empirical legal research with primary legal data sources collected through interviews with respondents at the Kelapa Lima Police Station as well as secondary legal data sources collected through literature studies or document studies. The results of the study found that: (1) efforts to overcome the crime of counterfeiting and circulation of counterfeit money in Kupang City, namely penal efforts and non-penal efforts carried out by the Kelapa Lima Police. (2) There are several obstacles faced in efforts to deal with the crime of counterfeiting and circulation of counterfeit money in Kupang City, including: the reluctance of the community to report the discovery of counterfeit money, the difficulty of collecting counterfeit money, the difficulty of arresting the perpetrators.